Content Analysis of Music Videos on the @Eunike.Tanzil Instagram Account’s Reels in the “Hum Me a Melody” Series - Muhammad Rafi Ansi Atallah (Universitas Negeri Surabaya, 2026)
This study aims to examine the process of creating musical content and packaging it for the series “Hum Me a Melody.” This qualitative study employed a “ ” approach, with data collection methods including interviews, observation, documentation, and literature review. The data analysis techniques used in this study were data reduction, data presentation, and conclusion. The data was tested for validity through source and technique triangulation. The first finding of the study concerns the content creation process, in which Eunike Tanzil went through the following stages of video and music creation: 1.) Preparation, 2.) Incubation 3.) Illumination 4.) Verification. The points above describe the stages from the emergence of an idea through the problem and solution to finalization. After that, the researcher moved on to a discussion of content packaging, which is divided into three aspects: 1) Visual, 2) Entertainment, and 3) Education. Overall, content packaging addresses the content itself.